2006
DOI: 10.1073/pnas.0603403103
|View full text |Cite
|
Sign up to set email alerts
|

Global roles of Ste11p, cell type, and pheromone in the control of gene expression during early sexual differentiation in fission yeast

Abstract: Fission yeast cells belong to one of two specialized cell types, M or P. Specific environmental conditions trigger sexual differentiation, which leads to an internal program starting with pheromone signaling between M and P cells, followed by mating, meiosis, and sporulation. The initial steps of this process are controlled by Ste11p, a master transcriptional regulator that activates the expression of cell type-specific genes (only expressed in either M or P cells) as well as genes expressed in both M and P ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
151
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(166 citation statements)
references
References 47 publications
8
151
0
6
Order By: Relevance
“…3B), which encodes a chaperone involved in loading of the centromere-specific histone H3 variant, CENP-A (36)(37)(38). Mc likely induces the expression of this locus because a previous study has shown that scm3 is expressed at higher levels in M cells, compared with P cells (35). Surprisingly, we also…”
Section: Resultsmentioning
confidence: 38%
See 4 more Smart Citations
“…3B), which encodes a chaperone involved in loading of the centromere-specific histone H3 variant, CENP-A (36)(37)(38). Mc likely induces the expression of this locus because a previous study has shown that scm3 is expressed at higher levels in M cells, compared with P cells (35). Surprisingly, we also…”
Section: Resultsmentioning
confidence: 38%
“…Scm3 is related to mammalian holiday junction-recognizing protein (46) and could potentially act together with Swi2-Swi5 to promote mating-type switching. We also found Mc localizing to map2 and map4, which are expressed specifically in P cells (35,39). Both of these genes possess long 5′ UTRs that contain several M boxes.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations